Establishment and related factors analysis of extrahepatic cholangiocarcinoma organoids - Zijun GONG; Jiaying LIU; Kun FAN; Sheng SHEN; Wenqing QIU; Xuanming LUO; Houbao LIU (Zhongguo Linchuang Yixue)
ObjectiveTo establish a cell bank of extrahepatic cholangiocarcinoma (ECC)-derived organoids and investigate the key factors influencing the organoids generation. Methods The tumor samples from patients with portal cholangiocarcinoma (pCCA) and distal cholangiocarcinoma (dCCA) were used to isolate cells, and these cells were cultured using three-dimensional (3D) technique to establish ECC organoids. Histological characteristics of the organoids were evaluated and identified through hematoxylin-eosin (HE) and immunohistochemistry stainings. The success rates of organoids generation from different tumor types were compared. And clinical characteristics of patients between successful and failure culture groups were compared. Results The success rates of organoids establishment from pCCA and dCCA were all low, with 42.4% (14/33), 51.9% (14/27), respectively. The tumor was larger in successful group than that in failure group (P＜0.001); there was no statistical difference in tumor differentiation status, microvascular invasion, and perineural invasion between the two groups. ConclusionsThe successful rate of ECC-derived organoids establishment is low, and larger tumor has higher successful culture rate.